2015
DOI: 10.1634/theoncologist.2014-0399
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of African Americans on Lung Cancer: A Qualitative Analysis

Abstract: Background. Disparities in incidence and mortality for lung cancer in African Americans are well documented; however, the extent to which disparities reflect differences in patient perceptions of tobacco and lung cancer treatment is unclear. The objective of this study was to explore African Americans’ knowledge of lung cancer, perceived risk, interest in smoking cessation, attitudes toward lung cancer treatment, and lung cancer diagnosis and treatment experiences. Patients and Methods. The cohort comprised 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The survival analysis indicated that among patients with type 2 CUP originating from the lung, white individuals tend to have a better prognosis than other individuals, which is in agreement with the findings of a previous study . Reviews suggest that the reasons for the wide racial disparities in lung cancer survival are complex and multifactorial, with contributions from treatment‐related factors, such as physician‐patient encounters and decision‐making, and barriers to access to high‐quality care, such as lower patient income or insurance coverage limits …”
Section: Discussionsupporting
confidence: 87%
“…The survival analysis indicated that among patients with type 2 CUP originating from the lung, white individuals tend to have a better prognosis than other individuals, which is in agreement with the findings of a previous study . Reviews suggest that the reasons for the wide racial disparities in lung cancer survival are complex and multifactorial, with contributions from treatment‐related factors, such as physician‐patient encounters and decision‐making, and barriers to access to high‐quality care, such as lower patient income or insurance coverage limits …”
Section: Discussionsupporting
confidence: 87%
“…2,17,2729 Reviews suggest that the reasons for the wide racial disparities in lung cancer survival are complex and multifactorial, with contributions from treatment-related factors, such as physician-patient encounters and decision-making, and barriers to access to high-quality care, such as lower patient income or insurance coverage limits. 3032 Unfortunately, although our study highlights 2 key determinants (race and stage) of survival differences between US states, it does not provide definite conclusions about all of the factors that may contribute to differences, because information on these factors is not available for all patients with cancer at a population-based level. It would be interesting to analyze the availability or receipt of optimal treatment by US state and race.…”
Section: Discussionmentioning
confidence: 83%
“…These have been found to be related to low income, tobacco advertisement, limited education, negative consequences of the cancer experience, loss of control, fatigue, social isolation, and lack of knowledge about causes, characteristics, and prognosis of the disease. [16] As well, research interest has been focused on the stress that lung cancer patients experience with findings of high levels of distress due to poor prognosis, with an accompanying sense of responsibility for the cancer, and the stigma associated with their disease as an illness of smokers. [17] Lehto (2014) also identified stigma among friends, family, and health professionals for people with lung cancer because the disease is so closely connected with smoking.…”
Section: Introductionmentioning
confidence: 99%
“…[7] According to Cataldo et al, [18] stigma among lung cancer patients can lead to negative outcomes including increased level of depression and diminished QOL. Lathan et al (2015) [16] used a qualitative approach to interview lung cancer patients and identified that negative thoughts and emotions, such as guilt, self-blame, and self-deprecation are common in this population. Similarly, Raleigh [8] found smokers with a lung cancer diagnosis often feel depression and guilt because they think that they are a burden to their families and friends.…”
Section: Introductionmentioning
confidence: 99%